Enhancing Students’ Learning Outcomes through Cooperative Learning: A Classroom Action Research - Setiawati Setiawati; Eva Antony (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to examine the effectiveness of cooperative learning using the greeting and questioning technique in achieving students’ mastery of chemistry learning outcomes on the topic of chemical bonding. Methodology: The study employed classroom-based action research conducted in several instructional cycles. Data were collected using achievement tests, classroom observations, and documentation. Achievement tests were administered to measure students’ learning outcomes, while observations were used to monitor teacher performance and student engagement throughout the learning process. Documentation supported the collection of contextual data related to the school, teachers, and students. Data analysis focused on the percentage of students achieving mastery learning criteria across cycles. Main Findings: The results revealed a progressive improvement in students’ mastery learning across instructional cycles. Classical mastery increased from 42.5% prior to the intervention to 47.5% in Cycle I, 72.5% in Cycle II, and reached 87.5% in Cycle III. These findings indicate that cooperative learning with the greeting and questioning technique effectively enhanced students’ learning outcomes and enabled the achievement of classical mastery in chemical bonding material. Novelty/Originality of this study: This study provides empirical evidence on the effectiveness of a cooperative learning strategy integrating greeting and questioning activities in improving mastery learning in chemistry, particularly on abstract topics such as chemical bonding, thereby contributing practical insights to classroom-oriented chemistry instruction.